Graftless Solutions for the Edentulous Patient (BDJ Clinician's Guides,, 2018)
This book, designed to meet the needs of clinicians, clearly explains the rationale and technique for the rehabilitation of fully edentulous patients utilizing traditional graftless concepts as well as zygomatic implant strategies when posterior support cannot be achieved by the former means. Considerations relevant to treatment planning and the biomechanics of immediate loading and zygomatic implants are first discussed. The techniques for placement of traditional tilted and zygomatic implants and for immediate loading of a full arch restoration are then described step by step. Detailed information and guidance are also provided on the different materials available for full arch restorations, laboratory aspects of the definitive restoration, maintenance of restorations, and management of prosthetic and surgical complications. The book concludes with a helpful series of clinical cases. Graftless Solutions for the Edentulous Patient is designed particularly for clinicians with experience in placing and restoring dental implants.